1989
DOI: 10.3109/09687688909082261
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinases in Neutrophils: A Review

Abstract: In chemotactic factor-stimulated neutrophils, rapid increases of intracellular levels of cyclic AMP, calcium, and diacylglycerol have been observed and may be linked to protein kinase activation. The study of the physiological role and regulation of protein kinases in the neutrophil and the identification of their substrates has provided valuable information on the molecular mechanism of neutrophil activation. The focus of this review is on those aspects of protein kinases that are relevant to neutrophil activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(5 citation statements)
references
References 99 publications
0
5
0
Order By: Relevance
“…5a). The reasons for this remain unclear, however, others have reported difficulty in demonstrating membrane-associated tyrosine kinases in neutrophils [40], suggesting that the complexes may not survive the extraction procedures used, perhaps due to release of hydrolytic enzymes during solubilization. An alternative possibility is that the complexes in neutrophils are very large, as suggested by the markedly granular staining pattern shown in Fig.…”
Section: Discussionmentioning
confidence: 94%
“…5a). The reasons for this remain unclear, however, others have reported difficulty in demonstrating membrane-associated tyrosine kinases in neutrophils [40], suggesting that the complexes may not survive the extraction procedures used, perhaps due to release of hydrolytic enzymes during solubilization. An alternative possibility is that the complexes in neutrophils are very large, as suggested by the markedly granular staining pattern shown in Fig.…”
Section: Discussionmentioning
confidence: 94%
“…Neutrophils generally have higher mobility than the other phagocytes, including both monocytes and macrophages (18). It has also been shown that when engulfing untargeted microparticles, the cellular pedestal of the neutrophils goes through protrusion in the direction of the target in the initial phases of phagocytosis, which shows their capability for remodeling their actin network during phagocytosis (37,38). The amount of cortical tension and viscosity is an order of magnitude higher for macrophages compared with neutrophils.…”
Section: Discussionmentioning
confidence: 99%
“…The involvement of PKC in the mechanisms underlying neutrophil stimulation by a variety of agonists (although not by MSU crystals) had been suggested by numerous studies based on pharmacological and biochemical approaches. PKC activators such as PMA, mezerein, bryostatin, and synthetic diacylglycerols potently stimulate the production of toxic oxygen metabolites and exocytosis, effects that can be prevented by PKC inhibitors (52)(53)(54). Despite the central role described for PKC in signal transduction, very little, if anything, is known about their participation in signaling pathways activated by MSU crystals in human neutrophils.…”
Section: Discussionmentioning
confidence: 99%